2018
DOI: 10.1038/s41551-018-0258-2
|View full text |Cite
|
Sign up to set email alerts
|

Acoustically targeted chemogenetics for the non-invasive control of neural circuits

Abstract: Neurological and psychiatric diseases often involve the dysfunction of specific neural circuits in particular regions of the brain. Existing treatments, including drugs and implantable brain stimulators, aim to modulate the activity of these circuits, but are typically not cell type-specific, lack spatial targeting or require invasive procedures. Here, we introduce an approach to modulating neural circuits noninvasively with spatial, cell-type and temporal specificity. This approach, called acoustically target… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 99 publications
3
98
0
1
Order By: Relevance
“…Such increased concentration after several injections can cause enhancement rates to elevate unintentionally. To avoid this issue, many groups have implemented delays between microbubble injections to allow for clearance 14,18,36 . Our results clearly show that even 15 min after delivery stopped there were enough circulating microbubbles for substantial BBB opening to occur (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such increased concentration after several injections can cause enhancement rates to elevate unintentionally. To avoid this issue, many groups have implemented delays between microbubble injections to allow for clearance 14,18,36 . Our results clearly show that even 15 min after delivery stopped there were enough circulating microbubbles for substantial BBB opening to occur (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that such considerations are not unique to chemogenetics but are shared by conventional brain-targeted gene therapies. New technologies such as acoustically-targeted chemogenetics 15 and systemically administered genetically-targeted vectors 16 offer further promise for minimizing invasiveness of such practices. Chemogenetics and related technologies are already greatly facilitating identification of disease-relevant neuron types and circuits at the preclinical level, and tools such as those reported here hold great promise for helping translate these groundbreaking studies into clinical strategies.…”
mentioning
confidence: 99%
“…in clinical trials, and new genome editing technologies have brought safe gene delivery a step closer to clinical practice 32 . Recently, several preclinical studies have shown that FUS in combination with microbubbles can transiently enhance the blood-brain barrier permeability for the noninvasive and localized delivery of intravenously injected AAVs to the mouse brain for optogenetics 33 and chemogenetics 34 . Currently, clinical trials are evaluating the feasibility and safety of the FUS technique for drug delivery to the brain [35][36][37] .…”
Section: Gene Therapy Methods Based On Viral and Other Vectors Have Amentioning
confidence: 99%